Development of a web application for park ticketing management - Benkhaled, MARWA; ZEBBAR, Sihem; Rapporteur: Mezrag, Fares (UNIVERSITY of M'SILA, 2022)
Work has increased on the Web application, especially on business applications, because this is one of the stimulating and important areas in our brief. We have provided a web application to manage park tickets, facilitate the ticket sales process, facilitate the process of controlling the park, and all that the park owner or customer needs, so we will work to improve performance to expand the functionality of the application. As much help as possible and hopefully in the future the web application will be extended and made available to developers and to improve and add new features
Keywords: Development ; web application ; park ; ticketing management